Experiences of patients talking about mental illness with their children: a qualitative study - Rapa, Elizabeth; Ilyas, Athif; de Cassan, Simone; Dalton, Louise J. (Frontiers in Psychology, 2025)
BackgroundMany adults with mental illness have dependent children; these parents must navigate decisions about whether and what to tell their children about the illness. Parents are often influenced by shame and guilt about their disorder, and a desire to protect their children from distress. Communication about parental mental illness can have important benefits for children’s psychological outcomes; professionals could be central in facilitating these conversations. This study explored parents’ experiences of talking to children about their mental illness and the role of their clinical team in this process.MethodsFifteen parents with a mental illness under NHS care in England participated in qualitative interviews. Audio recordings were transcribed verbatim and analyzed using an inductive coding approach following the principles of thematic analysis.ResultsThematic analysis identified 4 themes: 1. Factors that affect what children are told about parental mental illness, 2. Perceived benefits of talking to children about parental mental illness, 3. Experience of ‘who’ talks to children about parental mental illness, 4. Role of healthcare professionals in supporting families to talk about parental mental illness. There was wide variation in what information was shared with children, influenced by fears about how to share particular diagnoses and the impact of the information on parents themselves and their family. Participants reported that no professionals had asked them what their children knew about their mental illness or offered advice on how to have these conversations, but all would have welcomed this guidance.ConclusionImproving communication about parental mental illness requires targeted training programs for professionals and age-appropriate resources for families. This study emphasizes the critical role of fostering effective communication about parental mental illness to enhance children’s mental health and strengthen family functioning.